(untitled) (Jurnal Proaksi, 2024)
The background of this research is that corruption is still a problem in every country. ACFE every year still provides reports on cases that occur in the world. One that can detect cases with reports from whistleblowers. ACFE reports every year that reports from whistleblowers are more effective. There is an increase in cases revealed due to whistleblowing. The purpose of this study was to determine whether attitudes, subjective norms, behavioral control, organizational commitment, organizational culture affect a person’s intention to do whistleblowing. The research method used is quantitative research by distributing questionnaires, the population in this study are employees in various divisions including the finance, bookkeeping, IT, HRD divisions with the results showing that attitudes, subjective norms, behavioral control, organizational commitment, and organizational culture affect a person’s intention to whistleblowing. The conclusion of this study is that the higher the attitude, subjective norms, behavioral control, organizational commitment, and organizational culture, the higher one’s intention to whistleblowing. Keywords: Planned of behavior’s theory, Organizational Commitment, Organizational Culture, Whistleblowing